Age-Stage, Two-Sex Life Tables of Megalurothrips usitatus (Bagnall) and Frankliniella intonsa (Trybom) on Different Bean Pods Under Laboratory Conditions: Implications for Their Competitive Interactions - Mengni Li; Zhengke Peng; Chaosong Guo; Yong Xiao; Fei Yin; Haibin Yuan; Zhenyu Li; Myron P. Zalucki (Insects)
As two major pests of cowpea in South China, bean flower thrips [Megalurothrips usitatus (Bagnall)] and flower thrips [Frankliniella intonsa (Trybom)] always occur on the same plant. In this study, the two-sex life table parameters of these two species were investigated on three bean pods: cowpea (Vigna unguiculata L. var. Chunqiu Wujiadou), snap bean (Phaseolus vulgaris L. var. Yonglong 3), and green bean (Phaseolus vulgaris L. var. Linghangzhe) using standard cut bean protocols. Longevity of female adult M. usitatus showed no significant difference on cowpea and snap bean, but was shortest on green bean, with the highest fecundity on snap bean, followed by cowpea and green bean. Longevity and fecundity of female adult F. intonsa were both highest on cowpea, followed by snap bean and green bean. On snap bean, the population parameters (R0, GRR, T) of M. usitatus were higher than F. intonsa, whereas r and λ were not different, suggesting that M. usitatus were more competitive on snap bean. On cowpea, the population parameters (R0, GRR, r, λ) of F. intonsa were higher than M. usitatus, suggesting a competitive advantage of F. intonsa on cowpea. To better mimic field conditions, we investigated the survival and fecundity of adult M. usitatus under two distinct scenarios: when they could feed directly on cut surfaces of cowpeas (standard lab protocol), and when they could not. Adult survival of M. usitatus is not significantly influenced by whether or not they fed directly on cut surfaces of cowpeas. However, a notable decrease in fecundity was observed in M. usitatus that fed on surface-covered cut pods. This suggested that direct feeding on cut surfaces of cowpea did have an impact on thrips’ fecundity, offering fresh perspectives for future research into the growth and development of thrips in a laboratory. Our study suggests that experiments involving cut surfaces may be misleading, and further investigations are ongoing to address these concerns.